Rancang bangun industri penyamakan Kulit buaya skala kecil - Suliestiyah Wiryodiningrat; Titik Purwati Widowati; Purwanti Purwanti (Majalah Kulit, Karet, dan Plastik, 1988)
This paper is prepared for a design of a small scales crocodile skins tanning factory, to produce leather for leather goods.The capacity of it will be 10 pieces/day wet salted crocodile skins.This factory will be profitable in the view of techno – economical aspect. The economical calculation are as follows : the total capital is fixed capital + working capital Rp. 138.149.750,78 the total production cost is variable cost a year + fixed cost a year = Rp.140.115.913,40 the variable cost for a year consists of labour salaries, maintenance, capital interest, depreciation and general expences ; the manufacturing cost is the total production cost divided by production capacity = Rp.48.651,36/piece.The profit calculation before taxing is Rp.49.964.086,60 after taxing is Rp.39.971.269,30. The pay out period calculation consists of the percentage of profit to return the capital (rate of return) before taxing is 36,17% and after taxing is 28,93%; the pay out period before taxing 2 years 8 months, after taxing 3 years 3 months.The break even calculation consists of the break even point is Rp.77.306.648,33, the percentage of break even point is 40,67% and the capacity of break even points is 1.171 pieces.